Patterns of land use, extensification, and intensification of Brazilian agriculture - Lívia C. P. Dias; Fernando M. Pimenta; Ana B. Santos; Marcos H. Costa; Richard J. Ladle (Global Change Biology, 2016)
Sustainable intensification of agriculture is one of the main strategies to provide global food security. However, its implementation raises enormous political, technological, and social challenges. Meeting these challenges will require, among other things, accurate information on the spatial and temporal patterns of agricultural land use and yield. Here, we investigate historical patterns of agricultural land use (1940–2012) and productivity (1990–2012) in Brazil using a new high‐resolution (approximately 1 km 2 ) spatially explicit reconstruction. Although Brazilian agriculture has been historically known for its extensification over natural vegetation (Amazon and Cerrado), data from recent years indicate that extensification has slowed down and was replaced by a strong trend of intensification. Our results provide the first comprehensive historical overview of agricultural land use and productivity in Brazil, providing clear insights to guide future territorial planning, sustainable agriculture, policy, and decision‐making.